Correction: Facile fabrication and photoelectrochemical properties of a one axis-oriented NiO thin film with a (111) dominant facet. Issue 1 (12th November 2014) - Kim, Chang Woo; Son, Young Seok; Pawar, Amol Uttam; Kang, Myung Jong; Zheng, Jin You; Sharma, Vivek; Mohanty, Paritosh; Kang, Young Soo
Abstract : Correction for 'Facile fabrication and photoelectrochemical properties of a one axis-oriented NiO thin film with a (111) dominant facet' by Chang Woo Kim et al., J. Mater. Chem. A, 2014, 2, 19867–19872.